Meta‐analysis of human connection to nature and proenvironmental behavior. Issue 1 (12th July 2019) - Whitburn, Julie; Linklater, Wayne; Abrahamse, Wokje
Abstract: Understanding what drives environmentally protective or destructive behavior is important to the design and implementation of effective public policies to encourage people's engagement in proenvironmental behavior (PEB). Research shows that a connection to nature is associated with greater engagement in PEB. However, the variety of instruments and methods used in these studies poses a major barrier to integrating research findings. We conducted a meta‐analysis of the relationship between connection to nature and PEB. We identified studies through a systematic review of the literature and used Comprehensive Meta‐Analysis software to analyze the results from 37 samples ( n = 13, 237) and to test for moderators. A random‐effects model demonstrated a positive and significant association between connection to nature and PEB ( r = 0.42, 95% CI 0.36, 0.47, p < 0.001). People who are more connected to nature reported greater engagement in PEB. Standard tests indicated little effect of publication bias in the sample. There was significant heterogeneity among the samples. Univariate categorical analyses showed that the scales used to measure connection to nature and PEB were significant moderators and explained the majority of the between‐study variance. The geographic location of a study, age of participants, and the percentage of females in a study were not significant moderators. We found that a deeper connection to nature may partially explain why some people behave more proenvironmentally than others and that the relationship is ubiquitous. Facilitating a stronger connection to nature may result in greater engagement in PEB and conservation, although more longitudinal studies with randomized experiments are required to demonstrate causation. Abstract : Article impact statement : Interventions designed to facilitate a stronger connection to nature may result in greater engagement in proenvironmental behavior. Abstract : Metaanálisis de la Conexión Humana con la Naturaleza y el Comportamiento a Favor del Ambiental Resumen: El entendimiento de los conductores del comportamiento de protección o destrucción ambiental es importante para el diseño e implementación de políticas públicas que fomenten la participación de las personas dentro del comportamiento a favor del ambiente (PEB, en inglés). Las investigaciones muestran que la conexión con la naturaleza está asociada con una mayor participación en el PEB. Sin embargo, la variedad de instrumentos y métodos que utilizados en estos estudios presentan una barrera importante para la integración de los resultados de las investigaciones. Realizamos un metaanálisis de la relación entre la conexión con la naturaleza y el PEB. Identificamos estudios por medio de una revisión sistemática de la literatura y utilizamos software de Metaanálisis Completo para analizar los resultados de 37 muestras ( n = 13, 237) y para examinar a los moderadores. Un modelo de efectos azarosos demostró una asociación positiva y significativa entre la conexión con la naturaleza y el PEB ( r = 0.42, 95% CI 0.36, 0.47, p < 0.001). Las personas que están más conectadas con la naturaleza reportaron una mayor participación en el PEB. Las pruebas estándares indicaron un efecto menor del sesgo de publicación en la muestra. Hubo una heterogeneidad significativa entre las muestras. Los análisis univariados categóricos mostraron que las escalas usadas para medir la conexión con la naturaleza y el PEB fueron moderadores significativos y explicaron la mayoría de la varianza entre estudios. La ubicación geográfica de un estudio, la edad de los participantes, y el porcentaje de mujeres en un estudio no fueron moderadores significativos. Encontramos que una conexión más profunda con la naturaleza puede explicar parcialmente por qué algunas personas se comportan más a favor del ambiente que otras y que dicha relación es ubicua. La facilitación de una conexión más fuerte con la naturaleza puede resultar en una mayor participación en el PEB y en la conservación, aunque se requieren estudios más longitudinales con experimentos aleatorios para demostrar la causalidad 摘要: 理解保护环境和破坏环境行为背后的驱动力, 对于设计和实施有效的公共政策以鼓励人们参与环保行动至关重要。已有研究表明, 与自然的联系和环保行动参与度之间存在相关性。然而, 这些研究使用了各种各样的工具和方法, 导致这些研究结果难以整合。因此, 我们对人与自然的联系和环保行为之间的关系进行了荟萃分析。我们通过系统文献综述筛选出相关研究, 并用综合荟萃分析软件分析了 37 个样本 ( n = 13, 237) 的研究结果以检验干涉变量。随机效应模型显示, 亲近自然与环保行为之间有显著的正相关关系 ( r = 0.42, 95% CI 0.36, 0.47, p < 0.001) 。更亲近自然的人自我报告的环保行为参与度也更高。标准检测分析表明, 样本中的研究发表偏差的影响很小, 而各样本间存在显著的异质性。单变量分类分析结果显示, 用于测定人与自然的联系和环保行为的尺度是重要的干涉变量, 解释了大部分的研究间差异。而研究地点、参与者年龄和性别都不是显著的干涉变量。我们还发现, 与自然更深层次的联系可能部分解释了为什么有些人更环保, 而且其间的相关性普遍存在。促进人与自然更紧密的联系或能推动人们更多地参与环保和保护行动, 尽管仍需要更多包含随机实验的纵向研究来证明因果关系。【翻译: 胡怡思; 审校: 聂永刚】